Correction: Evolution of important glucosinolates in three common Brassica vegetables during their processing into vegetable powder and in vitro gastric digestion. Issue 2 (29th January 2020) - Kuljarachanan, Thitima; Fu, Nan; Chiewchan, Naphaporn; Devahastin, Sakamon; Chen, Xiao Dong
Abstract : Correction for 'Evolution of important glucosinolates in three common Brassica vegetables during their processing into vegetable powder and in vitro gastric digestion' by Thitima Kuljarachanan et al., Food Funct., 2020, DOI: 10.1039/c9fo00811j.